Happiness, Instrumentality and Expressiveness in Two Latin American Samples: Mexico and Bolivia - Díaz-Loving, Rolando (2018)
This study had two objectives: (1) to assess the effect that sex and place of origin have on levels of happiness and gender traits, and (2) to evaluate the relationship between happiness and gender traits on men and women from Mexico and Bolivia. The study population consisted of 998 volunteers: 583 Bolivian (293 men, 290 women) and 425 Mexicans (208 men, 207 women) aged between 18 and 64 years. To assess happiness, we used Alarcón’s Happiness Scale (2006). To assess gender, we used the Instrumentality and Expressiveness Attributional Dimensions Scale (EDAIE). A two-way analysis of variance (ANOVA) [sex (man-woman) x place of origin (Bolivia-Mexico)] was used to evaluate the interaction effect on three happiness and four gender factors. The Pearson product-moment correlation coefficient was used to measure the relationship between them. The ANOVA showed interaction effects of sex x place of origin only on two gender factors. The Pearson correlation coefficient showed that positive instrumentality and expressiveness are associated with optimal levels of happiness. The results are discussed in terms of cultural characteristics, such as individualism-collectivism, place of origin, sex, and happiness/well-being theories.